Legal guarantees to protect the buyer in the real estate sale contract (Damascus University Journal for legal sciences, 2024)
Real estate ownership enjoys great importance in our society, and it has expanded to include all its economic and legal activities, in addition to the moral and social value represented by owning a property. The contract or third parties, this does not mean that the unregistered real estate sale contract is void of any effect. Rather, it remains a consensual contract productive for all its effects, except for the transfer of ownershipwhere it imposes a set of obligations on both the seller and the buyer, where the seller must deliver the sale and ensure exposure, entitlement and hidden defects protection The right of the buyer before registration, and in return, the registration in the real estate registry by the buyer provides the guarantees of this protection if it is in good faith, as its registration has absolute evidentiary power.
Keywords: Buyer Protection; Unregistered Real Estate Sale Contract; Registered Real Estate Sale Contract; Legal Record